Heat Stress in Japanese Quails (Coturnix japonica): Benefits of Phytase Supplementation - Apolônio Gomes Ribeiro; Raiane dos Santos Silva; Dayane Albuquerque da Silva; Júlio Cézar dos Santos Nascimento; Lilian Francisco Arantes de Souza; Edijanio Galdino da Silva; José Evangelista Santos Ribeiro; Danila Barreiro Campos; Clara Virgínia Batista de Vasconcelos Alves; Edilson Paes Saraiva; Fernando Guilherme Perazzo Costa; Ricardo Romão Guerra (Animals)
In tropical and subtropical climate regions, heat stress is one of the main causes of production losses in laying quails, aggravated by the antinutritional effects of the phytate in diet ingredients, which negatively affect the bioavailability of minerals, especially calcium and phosphorus. This situation results in a reduction in production and the quality of eggs from commercial laying quails. Several nutritional strategies are utilized to reduce the adverse effects of high temperatures and antinutritional factors such as phytate. Among these strategies, the use of exogenous enzymes, such as phytase, stands out as a viable alternative. Phytase breaks down phytate molecules, optimizing the absorption of essential minerals and improving productive performance and egg quality under unfavorable conditions. Specifically, it is recommended to use 1500 FTU of phytase, as it not only reduces the effects of thermal stress but also enhances eggshell thickness and calcium absorption. In this context, this bibliographic review sought to produce a document demonstrating the beneficial effects of the phytase enzyme on the hydrolysis of the phytate molecule, the availability of calcium for Japanese quails (Coturnix japonica), and its implications in thermal stress due to heat.